2019
DOI: 10.1038/s41598-019-42131-y
|View full text |Cite
|
Sign up to set email alerts
|

High Skp2 expression is associated with a mesenchymal phenotype and increased tumorigenic potential of prostate cancer cells

Abstract: Skp2 is a crucial component of SCF Skp2 E3 ubiquitin ligase and is often overexpressed in various types of cancer, including prostate cancer (PCa). The epithelial-to-mesenchymal transition (EMT) is involved in PCa progression. The acquisition of a mesenchymal phenotype that results in a cancer stem cell (CSC) phenotype in PCa was described. Therefore, we aimed to investigate the expression and localization of Skp2 in clinical samples from patients with PCa, the association of Skp2 with E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 45 publications
3
10
0
Order By: Relevance
“…The stemness phenotype was reduced in cells with a silenced Skp2 . Moreover, Skp2 downregulation diminished the subpopulation of CD44 +/ CD24 − PCSC, which further supports the notable involvement of Skp2 in PCa stemness ( Simeckova et al, 2019 ). Using lineage retracing, Yoo et al identified a subpopulation of Bmi1+ Sox2+ CRPC cells as a potential source of in vivo disease recurrence.…”
Section: Pca Microenvironment and Cancer Stem/progenitor Cell Markerssupporting
confidence: 70%
“…The stemness phenotype was reduced in cells with a silenced Skp2 . Moreover, Skp2 downregulation diminished the subpopulation of CD44 +/ CD24 − PCSC, which further supports the notable involvement of Skp2 in PCa stemness ( Simeckova et al, 2019 ). Using lineage retracing, Yoo et al identified a subpopulation of Bmi1+ Sox2+ CRPC cells as a potential source of in vivo disease recurrence.…”
Section: Pca Microenvironment and Cancer Stem/progenitor Cell Markerssupporting
confidence: 70%
“…We have previously shown that a high Gleason score is associated with higher Skp2 and lower E-cadherin expression in a retrospective cohort of 101 patients ( Table 1 ) [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Next, we aimed to perform functional experiments, and we first made a screen of Skp2, Slug, and other proteins in three sets of prostate epithelial cell lines (PC3, DU145, and E2) and their mesenchymal counterparts. We have already reported that high Skp2 expression is associated with a mesenchymal phenotype and increased tumorigenic potential of DU145 prostate cancer cells [ 17 ]. These cells had a very low expression of Slug ( Figure 3 ), which is in concordance with other studies [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SKP2 is an oncogene that encodes a protein that regulates cell cycle entry and G 1 /S transition through a negative feedback loop targeting p21 and p27 degradation, thereby inhibiting cyclin-dependent kinases [ 85 , 86 ]. SKP2 overexpression has been already described in BrCa and PCa, contributing to the development and proliferation of these tumors, the acquisition of a mesenchymal phenotype, and the resistance to radio- and chemotherapy [ 87 , 88 , 89 , 90 ], being a potential therapeutic target [ 73 ]. Accordingly, [C16Pyr][Amp] showed promising results by reducing the SKP2 mRNA levels in the BrCa and PCa cell lines.…”
Section: Discussionmentioning
confidence: 99%